1980
DOI: 10.2466/pr0.1980.47.3f.1307
|View full text |Cite
|
Sign up to set email alerts
|

Coital Experience and Definition of Masculinity and Femininity by College Students

Abstract: Recent changes in sexual behavior of unmarried college students raise the question as to whether or not they are accompanied by changes in conceptions of masculinity and femininity on the part of the students. Changes in conceptions of masculinity and femininity might be the consequence of differential selection into coital activity or of new role learning by those who are coitally active. Data are presented from a study of sexual behavior of 823 college students which support the latter hypothesis for males b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Little prior research has examined how individuals understand the composition of gender/sex categories, and to what extent those understandings might be heterogeneous. While there is evidence of considerable cross-cultural variation in the meanings attached to gender/sex categories, particularly femininity/masculinity and womanhood/manhood (Jandt & Hundley, 2007; Tan, Shaw, Cheng, & Kim, 2013; Williams & Best, 1990), only a few studies have explored variation within a single cultural context by examining personal definitions of these concepts (Hoffman et al, 2005; Hunter & Davis, 1994; Kallen, Moore, & Stephenson, 1980; Myers & Gonda, 1982). However, these studies all have suggested considerable heterogeneity in personal definitions of gender/sex categories, particularly femininity/masculinity.…”
Section: Individuals’ Definitions Of Gender/sex Categoriesmentioning
confidence: 99%
“…Little prior research has examined how individuals understand the composition of gender/sex categories, and to what extent those understandings might be heterogeneous. While there is evidence of considerable cross-cultural variation in the meanings attached to gender/sex categories, particularly femininity/masculinity and womanhood/manhood (Jandt & Hundley, 2007; Tan, Shaw, Cheng, & Kim, 2013; Williams & Best, 1990), only a few studies have explored variation within a single cultural context by examining personal definitions of these concepts (Hoffman et al, 2005; Hunter & Davis, 1994; Kallen, Moore, & Stephenson, 1980; Myers & Gonda, 1982). However, these studies all have suggested considerable heterogeneity in personal definitions of gender/sex categories, particularly femininity/masculinity.…”
Section: Individuals’ Definitions Of Gender/sex Categoriesmentioning
confidence: 99%